The cultural rhetoric of capital punishment in Colonial America through the early Republic, 1641-1792 - Barton, John Cyril (The Elgar companion to capital punishment and society, 2024)
Once a worldwide leader in the movement to abolish the death penalty, the United States now stands virtually alone among leading nations in its use of the ultimate punishment. Focusing on the Colonial period through the Revolutionary era, this chapter examines the early history of capital punishment in America in terms of law, culture, and literature. It gives particular attention to what the author calls the cultural rhetoric of capital punishment: that is, the prominent arguments, tropes, and narratives through which the death penalty has been legitimated and supported, challenged, and contested, during this formative-and transformative-period in the institution’s development. The essay emphasizes the peculiarities of capital punishment as practiced in America and concludes with a brief discussion of death-penalty abolitionism in post-Revolutionary period through the antebellum era.